IMPLEMENTASI PILOT PROJECT ELEKTRONIK KTP DI KECAMATAN GONDOKUSUMAN YOGYAKARTA - , NOVA AGUNG BUDIONO, S.SOS; , Dr. Erwan Agus Purwanto, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Government's efforts to improve the residence system is using well regulated population administration, where there will be ID cards that are single, accurate and integrated with data nationally. Under Law no. 23 of 2006 Article 64 Paragraph 3, which reads where the ID card must provide a space that contains the security code and electronic recording important events, from this, born electronic ID (e-ID). In an e-ID cards have a chip that can contain the fingerprint technology in which the uniqueness of fingerprints that can only be owned by one person, so that the population number identity (NIK) and ID cards can be singular. E-ID card itself is one form of e-government applications, in transact class. This application of electronic identity cards (e-ID) has been done by several countries in Europe. Before implementing this program extensively, the government made a pilot project in some designated areas, one in District Gondokusuman, Yogyakarta. By learning from the experience of countries that have applied in advance, this study wanted to evaluate the implementation of pilot projects in that district. Where the goal is to see the performance of the implementation of e-ID card pilot project in District Gondokusuman and factors influencing it. The results of this research can improve or add to policies regarding the implementation of e-ID card in Indonesia. In this research uses a qualitative approach. Where primary data obtained through interviews the project implementers and some residents who were invited to make an e-ID card. While the secondary data obtained through surveys, to get a perception of quality of service from people who have made e-ID card. Obtained a sample of 195 people, using simple random sampling technique, with an error rate of 7% and 95% confidence level Target to be achieved in this pilot project is 26,000 who must make the e- ID card. Within a period of four months starting from October, then the results reached only 10. 162 per 10 January 2010, or 39.08% and then extended until the end of Ferbuari 2010 reached 83.23% The conclusion of this study, indicates that the performance of the implementation of e-ID card pilot project in District Gondokusuman less effective. The problem of socialization that does not invite stakeholders other than the target group, implementation of which is divided into two stages and the lack of infrastructure. In addition, services provided is also one of less effevtiveness. For example, residents received an e-ID card after a waiting period of two months, a bad photo quality and acceptance of e-ID card at the bank that still questionable. The most successful factor that influencing implementing of pilot project in District Gondokusuman is the executing agency.